2017
DOI: 10.1177/0033294117726076
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Personality on Physical Activity Among College Students: Examining Executive Function as a Potential Moderator

Abstract: Objective The purpose of this study was to examine the relationship between personality and physical activity, with a specific focus on whether executive function moderates this relationship. Methods One hundred twenty-six young adults provided complete data at baseline and the five-month follow-up assessment. Executive function was assessed via the parametric Go/No-Go computer task; outcome measures of parametric Go/No-Go were mean reaction time and percent of correct target detection across executive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The study design was a prospective study. Details on the study design can also be found in our previous work ( Joyner & Loprinzi, 2018 ), which evaluated the association between personality and physical activity and whether executive function moderated this relationship. In the present paper, we extend these previous findings by evaluating a multitude of additional collected variables, including other behaviors (e.g., smoking, diet, sleep, alcohol).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study design was a prospective study. Details on the study design can also be found in our previous work ( Joyner & Loprinzi, 2018 ), which evaluated the association between personality and physical activity and whether executive function moderated this relationship. In the present paper, we extend these previous findings by evaluating a multitude of additional collected variables, including other behaviors (e.g., smoking, diet, sleep, alcohol).…”
Section: Methodsmentioning
confidence: 99%
“…As described elsewhere ( Joyner & Loprinzi, 2018 ), recruitment of individuals included 200 undergraduate and graduate students from a university in the South of the United States for baseline assessments. Participants were recruited via a convenience-based sampling approach.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular and adequate training since childhood should not only lead to the development of fitness and motor performance, but also to the development of a series of personal traits of the individual (Kahlin et al, 2016;Joyner & Loprinzi, 2018). Many of those personal traits are considered to be the predictor for adherence to physical activity (Annesi, 2004).…”
Section: Introductionmentioning
confidence: 99%